Improving Students’ Motivation in Learning English Through Cooperative Learning Strategy by Using Media - Mandra Saragih; Ratih Utami (Universitas Muhammadiyah Tangerang, 2020)
This study deals with the improvement of students’ motivation in learning English through cooperative learning strategy assisted by attractive media. This study was conducted at SD Muhammadiyah 2 Medan, which located on Jl. Mustafa. No.1, Glugur Darat I, Medan Timur. The subject of the study is the grade six of 2019/2020 academic year. Classroom action research is applied in this study consist of two cycles, in which each cycle consists of four stages; planning, action, observation, and reflection. The data are obtained from both of observation and test. The qualitative data is analyzed through Miles and Huberman approach, while quantitative data is figured out through the formula . The result denotes that there are only 21 out of 43 students achieve 75 and over in cycle 1, whereas in cycle 2 there is significantly increasing number of students passing 75 and over with 43 students or 100%. In addition, learning activities become more active and creative. It is inferred that there was significant improvement on students’ motivation in learning English through cooperative learning strategy.